Laterality of the frontal aslant tract (FAT) explains externalizing behaviors through its association with executive function. Issue 2 (27th September 2018) - Garic, Dea; Broce, Iris; Graziano, Paulo; Mattfeld, Aaron; Dick, Anthony Steven
Abstract: We investigated the development of a recently identified white matter pathway, the frontal aslant tract (FAT) and its association with executive function and externalizing behaviors in a sample of 129 neurotypical male and female human children ranging in age from 7 months to 19 years. We found that the FAT could be tracked in 92% of those children, and that the pathway showed age‐related differences into adulthood. The change in white matter microstructure was very rapid until about 6 years, and then plateaued, only to show age‐related increases again after the age of 11 years. In a subset of those children (5–18 years; n  = 70), left laterality of the microstructural properties of the FAT was associated with greater attention problems as measured by the Child Behavior Checklist (CBCL). However, this relationship was fully mediated by higher executive dysfunction as measured by the Behavior Rating Inventory of Executive Function (BRIEF). This relationship was specific to the FAT—we found no relationship between laterality of a control pathway, or of the white matter of the brain in general, and attention and executive function. These findings suggest that the degree to which the developing brain favors a right lateralized structural dominance of the FAT is directly associated with executive function and attention. This novel finding provides a new potential structural biomarker to assess attention deficit hyperactivity disorder (ADHD) and associated executive dysfunction during development. Abstract : We investigated the development of a recently identified white matter pathway, the frontal aslant tract (FAT) and its association with executive function and externalizing behaviors in a sample of 129 neurotypical male and female human children ranging in age from 7 months to 19 years. We found that the FAT could be tracked in 92% of those children, and that the pathway showed age‐related differences into adulthood. We also found that the degree of right lateralization of the tract predicted better executive function and fewer attention problems. These findings suggest that the degree to which the developing brain favors a right lateralized structural dominance of the FAT is directly associated with executive function and attention.